Thymol Affects Congruency Between Olfactory and Gustatory Stimuli in Bees - Chapuy, Clara (Sci Rep, 2019)
Honey bees learn to associate sugars with odorants in controlled laboratory conditions and during foraging. The memory of these associations can be impaired after exposure to contaminants such as pesticides. The sub-lethal effects of acaricides such as 5-methyl-2-(propan-2-yl)-phenol (thymol) introduced into colonies to control varroa mites are of particular concern to beekeeping, due to detrimental effects of some acaricides on bees. Here we assess whether various odorant/sugar pairs are identically memorized in a differential appetitive olfactory conditioning experiment and whether this learning is affected by thymol exposure. Responses to odorants in retrieval tests varied according to the sugar they were paired with, a property called congruency. Interestingly, congruency was altered by pre-exposure to some thymol concentrations during retrieval tests, although electroantennography recordings showed it left odorant detection intact. This highlights the importance of taking into account subtle effects such as odor/sugar congruency in the study of the effect of pesticides on non-target insects, in addition to the simpler question of memory impairment.